(untitled) (Innovative professional education, 2025)
The article examines the issue of international cooperation in the development of vocational education in Ukraine through the involvement of European grant programs. The opportunities provided by European funds and organizations for the modernization of vocational education in Ukraine are analyzed. Special attention is given to programs such as Erasmus+, Horizon Europe, and other initiatives aimed at improving the quality of education, implementing innovative methodologies, and fostering international partnerships. The article highlights the role of international funding in improving curricula, training teaching staff, and developing modern educational infrastructurе